Facile preparation of sulphur-doped graphene quantum dots for ultra-high performance ultraviolet photodetectors - Gao, Shuxiong; Tang, Libin; Xiang, Jinzhong; Ji, Rongbin; Lai, Sin Ki; Yuan, Shouzhang; Lau, Shu Ping (New journal of chemistry, 2017)
Sulphur-doped graphene quantum dots (S-GQDs) were prepared in this work by a novel and facile method using the co-combustion (T-X-J method) of a liquid mixture of paraffin oil and carbon disulphide (CS 2 ). Ultra-high performance ( R : 307 A W −1 ; D *: 1.5 × 10 14 Jones) ultraviolet photodetectors based on S-GQDs were fabricated under ambient conditions, shedding light on the fabrication of graphene based high-performance optoelectronic devices.